Design and manufacture of multi-function electric nursing bed. Issue 5 (June 2019) - Wang, Shigang; Shi, Wei; Liang, Yinghuai; Huang, Longjun; Huang, Zhanqiang
Abstract: With the acceleration of population aging, the service of nursing industry is facing severe challenges. Medical and social insurance systems are facing unprecedented pressure. Therefore, the demand for nursing beds for elderly patients is increasing. In view of this phenomenon, the basic structure and functional principle of the multi-functional electric nursing bed designed for the elderly who lack self-care ability and the patients with mobility inconvenience are discussed in detail. Based on ergonomics, the overall design of nursing bed was carried out. According to the relevant standards and research results, the design principles and functional requirements of nursing bed were formulated, and the overall design of nursing bed body was completed. The top-down method was used to complete the design of nursing bed control system. The bed can help patients to turn over, sit up, bend knees, and defecate and other functions, solve many inconveniences in the process of nursing patients, thereby improving the service of nursing industry, and effectively promoting the development of medical and health care.